TATO DALAM KEHIDUPAN REMAJA (STUDI KASUS REMAJA PENGGUNA TATO DIKOTA PEKANBARU) - Anggelina JH, Liga; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research starts from a growing fascination with tattoos of indigenous traditions and culture into popular culture, pop culture even a unique work of art which is now many urban teens life accompany. Tattoos are images or symbols on skin body carved by using a type of needles and decorated with colorful pigments. Now this tattoo is already wearing the modern tools. At the time many tattoo enthusiasts at this time in teenagers, as for the reason the teenagers wears a tattoo of the search for identity so easily influenced by the attractive values, environmental conditions and is easy to make changes, and the children of the family removed wear tattoos as a symbol of liberation.This research aims to know the factors cause teens to wear on his body as well as to analyze how the meaning of the tattoo itself by teen users of the tattoo in city Pekanbaru. This research method using qualitative descriptive.The cases in this study a total of 10 subjects taken using the technique of snow ball having regard to the criteria.The results of this study showed that the use of tattoos in teenagers is because of the influence of friends as well as trend and fashion as a lifestyle and the meaning of tattoos in teenagers user tattoo is as an expression of feelings, art, spirituality (trust), to make it look cool and as fashion trends.Keywords: Tattoos, Teenager, Meaning Tattoos